Emerging soil contamination by hexamethylene and toluene diisocyanates in China: Distribution characteristics and influencing factors - Xiaomu Cao; Xuelong Cao; Yan Liu; Qiuning Hu; Qi Yan; Jiahe Zhuang; Yuqing Liang; Yongming Luo; Defu He (Environmental Pollution, 2026)

Parameterization of ground ice dynamics in permafrost models: Advances, challenges, and future directions - Yifan Wu; Guojie Hu; Lin Zhao; Zhe Sun; Bowen Zhang; Yao Xiao; Defu Zou; Guangyue Liu; Xiaofan Zhu; Tonghua Wu; Xiaodong Wu; Wenxin Zhang; et al. (Earth-Science Reviews, 2026)

Dynamics simulation on microstructural properties evolution of high-alkali coal slag in reducing conditions: The roles of alkali oxide, alkaline earth oxides, and iron oxide - Guowei Ma; Junyan Gu; Maoyun Luo; Chang’an Wang; Jiamiao Liu; Yonggang Zhao; Lin Zhao; Limin Wang; Wanzhu Wu; Hu Wang; Defu Che (Fuel, 2026)

Valorization of illite-bearing mine tailings in LC3 binders enabled by CO2-Mineralized steel slag - Yuming Huo; Haiyong Hu; Yulong Jiang; Defu Zhu; Zekun Xu (Sustainable Chemistry and Pharmacy, 2026)

Deciphering the impact of soil nutrients on diversity and functional genes of bacteria within the upper 3 m soil under different land cover types - Xiaoying Fan; Xiaodong Wu; Qian Luo; Tonghua Wu; Guimin Liu; Defu Zou; Guojie Hu; Yadong Liu; Xianhua Wei; Xuchun Yan; Yongxiang Liu; Sizhong Yang; et al. (CATENA, 2026)

Soil texture regulates soil C mineralization by C substrates and microbial characteristics under vegetation restoration - Lingbo Dong; Weifang Hu; Defu Wang; Hailong Zhang; Jianzhao Wu; Jiwei Li; Rula Sa; Zhouping Shangguan; Lei Deng (Plant and Soil, 2026)

Experimental Investigation into the Influence of Water Saturation on the Tensile Failure Behavior of Diaspore-Type Bauxite: Implications for Underground Mining of Bauxite - Defu Zhu; Wenshuo Hu; Yalin Li; Qingsheng Bai; Yongjie Jia; TengFei Fu; Gan Feng; Yujiang Zhang; Xiaosong Sun; Yongqing Lin; Dingwei Sun (Rock Mechanics and Rock Engineering, 2026)

Full-scale experimental study of flame behavior and thermal distribution in utility tunnel fires - Xiaojiang Liu; Zhao-Dong Xu; Jun Dai; Jiayu Che; Zhong-Wei Hu; Defu Che (Tunnelling and Underground Space Technology, 2026)

Effects of Acute Heat Stress and Hypo-Salinity Exposure on Sea Cucumber Apostichopus japonicus by Widely Targeted Metabolomics Analysis - Qi Wang; Defu Gao; Bin Zhao; Wei Hu (Journal of Marine Science and Engineering, 2026)
Temperature and salinity are key environmental factors for sea cucumber (Apostichopus japonicus) aquaculture. To better understand the molecular regulation mechanisms of A. japonicus under extreme environmental conditions, we collected metabolomic data from a control group (C: 16 °C, 30 salinity), a heat-stress group (HT: 30 °C, 30 salinity), a hypo-salinity group (LS: 16 °C, 20 salinity), and a heat plus hypo-salinity group (HL: 30 °C, 20 salinity). Liquid chromatography–mass spectrometry-based metabolomics was used to measure the changes in endogenous metabolites in the body wall of A. japonicus and detect differential metabolites and associated metabolic pathways. The results of metabolomic profiling identified a total of 349 secondary metabolites, enriched mainly in unsaturated fatty acid metabolism, cAMP signaling pathway, pantothenic acid and coenzyme A biosynthesis, as well as vitamin metabolism. Compared to the control group, levels of amino acids and lipids were enhanced during adaptation to high-temperature stress (HT and HL groups). Levels of pantothenic acid content increased in the LS group compared with its content in the control group, which suggests that stress promoted the TCA cycle in the body of A. japonicus, providing energy for movement. A. japonicus may adjust energy metabolism by altering pathways or adapt to environmental changes by regulating the activities of certain enzymes to maintain life activities and metabolic homeostasis. In response to these stresses, A. japonicus metabolism increased to bolster its antioxidant capacity and maintain cellular homeostasis and organismal stability. These results clarified the complex physiological processes involved in the response to stress and the maintenance of metabolism of the A. japonicus. This study provides novel insights into the metabolic regulation mechanisms that enable A. japonicus to cope with heat and hypo-salinity stresses.

The crucial role of ground ice in slowing permafrost degradation - Guojie Hu; Zhe Sun; Lin Zhao; Deliang Chen; Defu Zou; Chien-Lu Ping; Wenxin Zhang; Yao Xiao; Guangyue Liu; Ren Li; Xiaodong Wu; Yifan Wu; et al. (Science Bulletin, 2026)

Benchmarking and lightweight correction of daily near-surface air temperature products over the Qinghai-Tibetan Plateau - Nan Zhou; Yao Xiao; Lin Zhao; Guojie Hu; Lingxiao Wang; Chong Wang; Ren Li; Guangyue Liu; Defu Zou; Xiangfei Li (Atmospheric Research, 2026)

High-resolution (30 m) mapping of permafrost distribution in the Genhe River Basin, Greater Khingan Mountains, Northeast China - Xueling Jiao; Lin Zhao; Defu Zou; Lingxiao Wang; Chong Wang; Yuanwei Wang; Guojie Hu; Erji Du; Yao Xiao; Guangyue Liu; Shibo Liu; Yuxin Zhang; et al. (Journal of Mountain Science, 2026)

Ctab-mediated core-shell Pd-based nanocatalysts: pore engineering and N-doping synergy for efficient phenol hydrogenation to cyclohexanone - Lu Shen; Defu Yin; Zewei Hu; Dongyu Liu; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Fuel, 2026)

Evaluation of stability and cooling engineering effectiveness of the Qinghai-Tibet transportation routes: A first comprehensive assessment using space geodetic observations - Lingxiao Wang; Lin Zhao; Shibo Liu; Huayun Zhou; Guojie Hu; Defu Zou; Erji Du; Guangyue Liu; Yao Xiao; Yueli Chen; Jianting Zhao; Wei Chen; et al. (Engineering Geology, 2026)

Spatial distribution of vegetation type in the Genhe River Basin based on multi-source data - Zhinan Zhou; Chong Wang; Lin Zhao; Defu Zou; Guangyue Liu; Shibo Liu; Lingxiao Wang; Guojie Hu; Zanpin Xing; Erji Du; Yao Xiao; Xueling Jiao (International Journal of Remote Sensing, 2025)

Lattice Boltzmann simulation on adsorption of sulfuric acid vapor by ash particles - Jiyun Ren; Chongjun Jiang; Fangfang Hu; Hui Wang; Yunhao Shao; Xinyu Liu; Zhang Wu; Feng Pan; Qidong Yang; Lei Deng; Defu Che (Fuel, 2025)

Quantifying the soil water content of the permafrost active layer using InSAR deformation - Erji Du; Lingxiao Wang; Lin Zhao; Huayun Zhou; Shibo Liu; Defu Zou; Guangyue Liu; Yao Xiao; Guojie Hu; Zhibin Li; Junqiang Gao; Chong Wang; et al. (Journal of Hydrology, 2025)

Research on the synergistic catalytic conversion of CO2 and its mechanism in a novel gliding arc plasma fluidized bed - Defu Kong; Xianhui Chen; Taohon Ye; Cheng Zhu; Haoxin Hu; Weidon Xia (Environmental Research, 2025)

Soil fauna Protaetia brevitarsis mediated polyethylene microplastic biodegradation - Jie Jiang; Yan Liu; Qiuning Hu; Qi Yan; Jiahe Zhuang; Xuelong Cao; Wei-Min Wu; Defu He (Science of The Total Environment, 2025)

Study on the mechanism of multiple sodium salts co-loading on ash fusibility and mineral evolution behaviors - Hongli Liang; Jinhao Yi; Yang Yang; Lei Zhang; Tao Ma; Weibin Chen; Hu Liu; Defu Che (Fuel, 2025)

Threshold-governed insulating and cooling effects of snow cover on alpine permafrost: evidence from the Qinghai–Tibet Plateau - Yao Xiao; Guojie Hu; Ren Li; Tonghua Wu; Xiaodong Wu; Guangyue Liu; Defu Zou; Zanpin Xing; Jimin Yao; Chong Wang; Lin Zhao (Agricultural and Forest Meteorology, 2025)

Improving the moving-grid permafrost model to reveal ground deformation and hydrothermal effects caused by permafrost evolution in the source region of the Yangtze river on the Qinghai-Tibet plateau - Zhe Sun; Lin Zhao; Guojie Hu; Shibo Liu; Yongping Qiao; Erji Du; Defu Zou; Guangyue Liu; Lingxiao Wang; Jianting Zhao (Environmental Modelling & Software, 2025)

Land cover types and depth regulate carbon and nitrogen cycle functional genes in permafrost regions on the Qinghai-Tibet Plateau - Xiaoying Fan; Xiaodong Wu; Dejincuo Ma; Tonghua Wu; Guimin Liu; Haiyan Xu; Defu Zou; Guojie Hu; Yadong Liu; Xianhua Wei; Xuchun Yan; Yongxiang Liu; et al. (Plant and Soil, 2025)

The surface features and internal structure of an integrated open system pingo in the source area of the Yangtze River on the Qinghai-Tibet Plateau - Guangyue Liu; Yao Xiao; Guojie Hu; Tonghua Wu; Xiaodong Wu; Lingxiao Wang; Changwei Xie; Defu Zou; Erji Du; Yonghua Zhao; Yingying Lu; Lin Zhao (CATENA, 2025)

Ground surface deformation in permafrost region on the Qinghai-Tibet Plateau: A review - Shibo Liu; Lin Zhao; Lingxiao Wang; Lin Liu; Defu Zou; Guojie Hu; Zhe Sun; Yuxin Zhang; Wei Chen; Xueying Wang; Meng Wang; Huayun Zhou; et al. (Earth-Science Reviews, 2025)

PdH as the hydrogen transporter for phenol hydrogenation reaction - Defu Yin; Zewei Hu; Yunxi Hou; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Chemical Engineering Journal, 2025)

Process and mechanism analysis of typical permafrost area surface deformation at two sites along the Qinghai-Tibet highway based on long-term leveling observation - Shibo Liu; Lin Zhao; Lingxiao Wang; Defu Zou; Guojie Hu; Zhe Sun; Huayun Zhou; Yongping Qiao (Science of The Total Environment, 2024)

Spatiotemporal changes and management measure to enhance ecosystem services in the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Yadong Liu; Xuchun Yan; Xiaoying Fan; Avirmed Dashtseren; et al. (Environmental Development, 2024)

Efficient and stable Pd catalyst confined in microporous carbon shells for phenol hydrogenation - Zewei Hu; Defu Yin; Hanli Zheng; Yunxi Hou; Lu Shen; Dongyu Liu; Wenman Liu; Ruixin Pang; Yue Liu (Chemical Engineering Journal, 2024)

Experimental investigation on product and temperature distribution in a continuous flow packed-bed reactor for dodecahydro-N-ethylcarbazole dehydrogenation - Jingwen Xue; Pengzhao Li; Pengfei Yu; Jinhao Yi; Tao Ma; Hu Liu; Defu Che (Chemical Engineering Journal, 2024)

Large variability in permafrost degradation over the Northern Hemisphere - Guojie Hu; Lin Zhao; Defu Zou; Xiaodong Wu; Ren Li; Xiaofan Zhu; Youqi Su; Tonghua Wu; Yifan Wu; Jie Ni (CATENA, 2024)

Facile synthesis of carbon black and sodium alginate based particles system for efficient solar desalination of highly concentrated brine - Jiwen Zhang; Xiaozhen Hu; Kaiyuan Shi; Haiyan Sun; Dejian Yang; Mutian Yang; Bo Xu; Zhengwen Xu; Defu Xu (Journal of Environmental Chemical Engineering, 2024)

Injectable NGF-loaded double crosslinked collagen/hyaluronic acid hydrogels for irregular bone defect repair via neuro-guided osteogenic process - Qingsong Jiang; Liaomin Zhou; Yi Yang; Hu Long; Liming Ge; Defu Li; Changdao Mu; Wenli Lai; Zhilang Xu; Yan Wang (Chemical Engineering Journal, 2024)

Effects of dietary Allium mongolicum Regel powder supplementation on the growth performance, meat quality, antioxidant capacity and muscle fibre characteristics of fattening Angus calves under heat stress conditions - Wangjing Liu; Huixia Gao; Jianjian He; Aihuan Yu; Chenxu Sun; Yaodi Xie; Haibo Yao; He Wang; Yueyan Duan; Jinsheng Hu; Defu Tang; Tao Ran; et al. (Food Chemistry, 2024)

New insight into oxygen vacancy and synergism in CuCeOx catalysts based on the toluene oxidation - Guangtao Hu; Zirui Zhang; Chang’an Wang; Guojie Li; Dandan Zhou; Jinshi Wang; Defu Che; Running Kang (Journal of Environmental Chemical Engineering, 2024)

Highly stereoselective hydrogenation of α‑pinene over Ir nanoparticles confined in SiO2 shells - Defu Yin; Zewei Hu; Mingya Liu; Jingyun Zhang; Hanli Zheng; Yunxi Hou; Shitao Yu; Lu Li; Shiwei Liu; Yue Liu (Chemical Engineering Journal, 2024)

Risk factors of vestibular migraine-related brain white matter lesions - Yu Shen; Defu Li; Qian Cao; Mengyao Hu; Zhou Hou; Lijun Xu; Yanping Li; Daojun Hong (Acta Neurologica Belgica, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

Water and heat coupling processes and its simulation in frozen soils: Current status and future research directions - Guojie Hu; Lin Zhao; Ren Li; Hotaek Park; Xiaodong Wu; Youqi Su; Georg Guggenberger; Tonghua Wu; Defu Zou; Xiaofan Zhu; Wenxin Zhang; Yifan Wu; et al. (CATENA, 2023)

Hydrogenation of N-ethylcarbazole with Hydrogen-Methane mixtures for hydrogen storage - Hu Liu; Jingwen Xue; Pengfei Yu; Yankang Zhang; Jinhua Wang; Defu Che (Fuel, 2023)

Long-term soil temperature dynamics of the Kunlun Pass permafrost region on the Qinghai-Tibetan Plateau - Guojie Hu; Lin Zhao; Tonghua Wu; Xiaodong Wu; Ren Li; Xiaofan Zhu; Defu Zou; Junming Hao; Wangping Li (Theoretical and Applied Climatology, 2022)

Comparison of the Homology Between Muskrat Scented Gland and Mouse Preputial Gland - Xiangyu Han; Yuanlin Jiang; Nuannuan Feng; Pengcheng Yang; Meishan Zhang; Weijiang Jin; Tianxiang Zhang; Zhixin Huang; Haoxi Zhao; Kexin Zhang; Shuqiang Liu; Defu Hu (Journal of Mammalian Evolution, 2022)

Effects of Chronic Stress on the Fecal Microbiome of Malayan Pangolins (Manis javanica) Rescued from the Illegal Wildlife Trade - Dingyu Yan; Defu Hu; Kaixiang Li; Baocai Li; Xiangyan Zeng; Jinyan Chen; Yimeng Li; Torsten Wronski (Current Microbiology, 2021)

Enhanced dewater efficiency for river sediment by top-to-bottom water transmitting channels with different materials - Zhuo Shi; Kewu Pi; Xuanming Huang; Yafei Shi; Ziwen Chen; Ruyu Tang; Zehui Hu; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2020)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Behavioral and physiological responses of forest musk deer (Moschus berezovskii) to experimental fawn manipulation - Wenxia Wang; Lan He; Shuqiang Liu; Torsten Wronski; Defu Hu (acta ethologica, 2016)

Acteoside reduces testosterone by inhibiting cAMP, p450scc, and StAR in rat Leydig cells - Shuqiang Liu; Junwen Zhang; Weixuan Li; Tianxiang Zhang; Defu Hu (Molecular & Cellular Toxicology, 2015)

Evaluation of fecal DNA preservation and extraction methods in Przewalski’s horse - Gang Liu; Sen Zang; Linhai Li; Xiaolong Hu; Shasha Zhao; Kai Li; Defu Hu (Conservation Genetics Resources, 2014)

Isolation and characterization of microsatellite loci from Gasterophilus pecorum (Diptera: Gasterophilidae) - Fang Cheng; Jianmei Yang; Dong Zhang; Defu Hu; Hongjun Chu; Jie Cao; Feng Jiang; Lan Bu; Kai Li (Conservation Genetics Resources, 2014)

Knockdown of ZNF403 inhibits cell proliferation and induces G2/M arrest by modulating cell-cycle mediators - Rui Guan; Xiao-Yan Wen; Jing Wu; Rongqi Duan; Huibi Cao; Simon Lam; Defu Hou; Youdong Wang; Jim Hu; Zhuchu Chen (Molecular and Cellular Biochemistry, 2012)